Twilight at Moorington Cross [large type] - Wilson, Abigail (Thorndike Press large print Christian romance series., 2022)
"Brushed cruelly aside by the only father figure she's ever known and then hospitalized by her arranged husband months before his death, Amelia Pembroke means to take control of her future at last, one way or another. Yet she knows all too well she faces an uphill battle, considering her transient sleeping spells are only getting worse. Cluett's Mesmeric Hospital has been something of a refuge for Amelia over the past year, even if it didn't exactly improve her condition. But when her doctor is murdered and her name surprisingly turns up in his will, her options take a drastic turn. She has thirty days to marry one of two named gentlemen--strangers to her--and she will inherit everything from her friend and doctor, Mr. Cluett. One simple decision and all her financial troubles are at an end. The only problem is it's not a simple decision anymore. Not when she's falling in love with another man. Ewan Hawkins has received his first assignment as an apprenticed solicitor: to update a man's will. Finally, a chance to prove to society that possessing a disfigurement won't hold him back. Thus, he means to do his job well. Of course, he never could have anticipated a murder, nor the strange clause added to the will--nor, most importantly, the charming widow who has found a way to capture his heart"--